CO-PERPETRATION IN CRIMINAL LEGISLATION IN BOSNIA AND HERZEGOVINA - Vasiljević, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
In the criminal legislation in Bosnia and Herzegovina, the participation of several persons in the commission of a criminal offense is regulated in the provisions of the general parts of Criminal Codes in accordance with the restrictive notion of the perpetrator. (Co)perpetration is clearly separated from complicity, where the starting point is the principle of limited accessory. In addition to the above, the Criminal Code of Bosnia and Herzegovina contains a solution based on the monistic understanding of the perpetrator, thus accepting the extensive-restrictive model of perpetration. Аuthor pays attention to the legal regulation of the model of co-perpetration in the criminal legislation in Bosnia and Herzegovina.
Keywords: co-perpetration, criminal legislation, Bosnia and Herzegovina